Intellectual property rights and foreign technology licensing in developing countries: An empirical investigation - Elisabetta Gentile (Asian Development Bank (ADB), 2017)
The paper addresses the question of whether expanded and strengthened protection of intellectual property (IP) fosters technology transfer to developing countries. Cross-sectional analysis of a representative sample of firms operating in 42 developing economies indicates that going from no IP protection to maximum IP protection is associated with a 65% increase in the predicted probability of licensing foreign technology for the subpopulation of affiliated firms, whereas the predicted probability is not significantly different from zero for unaffiliated firms. We also find evidence that the environment in which a firm operates moderates the relationship of IP protection and firm-level technology licensing: while going from no IP protection to maximum IP protection is associated with a 47% increase in the predicted probability of licensing foreign technology for firms operating in upper-middle-income countries, there is at best no significant correlation for firms operating in lower-middle-income and lowincome countries.
Keywords: L24; O14; O19; O34; 330; developing countries; intellectual property rights; technology licensing; TRIPSAgreement